One teacher educator’s strategies for encouraging reflective practice - Russell, Tom (Frontiers in Education, 2022)
Teaching reflective practice to beginning teachers requires significant changes in a teacher educator’s implicit assumptions about how individuals learn to teach. Teaching reflective practice also requires significant changes in a teacher educator’s teaching practices. The familiar teach-them-theory-and-then-let-them-practice approach assumes that learning is complete before practice begins. In contrast, reflective practice in professions involves learning from firsthand experience and recognizes that the process of learning theory and research is incomplete before personal practice begins. Teaching reflective practice also requires recognizing that terms such as reflect and reflection are everyday words with multiple meanings and uses and little direct connection to reflective practice. The following argument, grounded in self-study methodology, describes indirect strategies for encouraging reflective practice. These strategies include an extended writing assignment focused on professional learning, teaching how to learn from personal experience, the unrecognized power of listening, and tickets out of class as listening and fostering metacognition. The argument closes with a summary of suggested strategies for encouraging reflective practice by those learning how to teach.